Subcutaneous fat mass in infancy and cardiovascular risk factors at school-age: The generation R study - Santos, S (2016)
OBJECTIVE:To examine the associations of infant subcutaneous fat with cardiovascular risk factors at school-age. METHODS:In a population-based prospective cohort study among 808 children, total subcutaneous fat (sum of biceps, triceps, suprailiacal, and subscapular skinfold thicknesses) and central-to-total subcutaneous fat ratio (sum of suprailiacal and subscapular skinfold thicknesses/total subcutaneous fat) at 1.5 and 24 months were estimated. At 6 years, body mass index, blood pressure, cholesterol, triglycerides, and insulin levels were measured. RESULTS:Infant subcutaneous fat measures were not associated with childhood blood pressure, triglycerides, or insulin levels. A 1-standard-deviation score (SDS) higher total subcutaneous fat at 1.5 months was, independently of body mass index, associated with lower low-density lipoprotein (LDL)-cholesterol levels at 6 years. In contrast, a 1-SDS higher total subcutaneous fat at 24 months was associated with higher total-cholesterol [difference 0.13 (95% confidence interval (CI) 0.03, 0.23) SDS] and LDL-cholesterol levels [difference 0.12 (95% CI 0.02, 0.21) SDS] at 6 years. There were no associations of central-to-total subcutaneous fat ratio with childhood cholesterol levels. CONCLUSIONS:These results suggest that infant total subcutaneous fat is weakly associated with cholesterol levels at school-age. Further studies are needed to assess the long-term cardiometabolic consequences of infant body fat.